Mayy Ziyāda, pioneer in the creation of modern Arabic literary criticism - Santos-de-la-Rosa, Inmaculada (Anaquel de Estudios Árabes, 2024)
This study refutes the theory promoted by a group of intellectuals close to Mayy Ziyāda's environment, who question her originality as a writer. Based on the analysis of excerpts from the correspondence between Mayy Ziyāda and Yaʿqūb Ṣarrūf, friend and director of the magazine al-Muqtaṭaf, the comments of the contemporary cultural elite are examined. In them, opinions are expressed not only about Ziyāda's work methodology, but also about her distinctive attributes as an author. These testimonies provide a new perspective on the literary contribution of this author, a relevant member of nahḍā literature.
Keywords: Modern Arabic literature; Mayy Ziyāda; Literary Criticism; Theory of literature; Nahḍa